Co-doped fluorescent material with reverse thermal quenching characteristics and preparation method and application thereof

By using co-doped fluorescent materials with reverse heat quenching characteristics, the problem of high-temperature thermal quenching of fluorescent materials is solved, and the temperature measurement range is widened and detection sensitivity is improved. It is suitable for contactless temperature sensors.

CN117384641BInactive Publication Date: 2025-04-04UNIV OF ELECTRONICS SCI & TECH OF CHINA
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311326830.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-10-13
Publication Date
2025-04-04
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing fluorescent materials have high temperature thermal quenching at high temperatures, resulting in a narrow temperature measurement range and low detection sensitivity, which limits the development of contactless optical temperature sensing technology.

Method used

A co-doped fluorescent material with reverse heat quenching characteristics, with the general chemical formula of Na3Ca4-x-yTbxEuyTeP3O15, was prepared by microwave solid phase synthesis method. The luminescence centers of the doped terbium ions (Tb3+) and europium ions (Eu3+) were located at 545nm and 617nm respectively.

Benefits of technology

The material exhibits excellent luminescence thermal stability, can effectively widen the temperature measurement range, and significantly improve detection sensitivity. The absolute sensitivity can reach 5.61×10-2K-1 and the relative sensitivity can reach 4.43% K-1.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117384641B_ABST
    Figure CN117384641B_ABST
Patent Text Reader

Abstract

The invention discloses a co-doped fluorescent material with anti-thermal quenching characteristics, a preparation method and an application thereof, and belongs to the technical field of fluorescent materials. The co-doped fluorescent material Na3Ca is obtained by mixing and grinding raw materials corresponding to the molar ratio of elements Na, Ca, Tb, Eu, Te and P in 3:(4-x-y):x:y:1:3, and then synthesizing the co-doped fluorescent material Na3Ca 4‑x‑y Tb x Eu y TeP3O 15 , where 0.01≤x,y≤0.2, has excellent thermal stability of luminescence and meets the requirements of working under high temperature conditions. With the increase of ambient temperature, the luminescence intensity shows a trend of first rising and then falling, showing the characteristics of reverse thermal quenching. It can be applied to non-contact temperature sensors, which can further expand the temperature measurement range of non-contact temperature sensors and significantly improve the temperature measurement sensitivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of fluorescent materials, and in particular relates to a co-doped fluorescent material with reverse thermal quenching characteristics, a preparation method and an application thereof. Background Art

[0002] Luminescence ratio thermometry, as an advanced non-contact optical temperature measurement technology, has attracted great interest. It uses the thermal response spectral characteristics of luminescent materials to provide accurate and fast temperature readings with high resolution under harsh conditions. Among various non-contact optical temperature measurement technologies, the luminescence intensity ratio (LIR) technology based on luminescent centers with different temperature responsiveness has become the most popular technology due to its high accuracy, simple operation and strong anti-interference ability.

[0003] At present, optical temperature measurement technology mainly uses infrared temperature measurement and single rare earth luminescent ion thermal coupling energy level luminescence intensity ratio temperature measurement. However, when infrared temperature measurement is affected by interference environment, it will have problems of large temperature measurement error and low sensitivity. For rare earth ion thermal coupling energy level luminescence intensity ratio temperature measurement technology, the thermal coupling condition needs to be met, that is, the energy level interval of the thermal coupling energy level must be between 200cm -1 ~2000cm -1 Therefore, the thermal coupling condition limits the further improvement of the detection sensitivity and signal detection discrimination of the temperature measurement scheme of the luminescence intensity ratio of the thermally coupled energy level of a single rare earth luminescent ion.

[0004] The two rare earth ion luminescence centers in co-doping can overcome the above-mentioned defects of the prior art, thereby providing a novel, highly sensitive, and high-signal discrimination optical temperature measurement method. However, the high-temperature thermal quenching phenomenon that is prevalent in phosphors will seriously affect the performance of fluorescent materials in the field of non-contact optical temperature measurement, making its temperature measurement range narrow and the detection sensitivity low. For example, patent CN202110246350.6 discloses luminescent materials based on cerium and europium activated aluminosilicates, as well as preparation methods and applications. Due to the high-temperature thermal quenching of the phosphor, the maximum temperature in its temperature measurement range is only 425K, and the absolute sensitivity is only 0.0188K. -1 , the relative sensitivity is only 1.35%K -1 . It can be seen that severe high-temperature thermal quenching effect will greatly reduce the temperature measurement performance, which seriously limits the development of high-sensitivity non-contact optical temperature sensing technology. Unfortunately, it is quite challenging to overcome the high-temperature thermal quenching effect and realize the application of non-contact optical temperature sensing technology at the same time. Therefore, it is necessary to explore new methods and formulate strategies to maintain or even improve the luminescence performance of phosphors at high temperatures, so as to realize non-contact optical temperature sensing technology. Summary of the invention

[0005] In view of the problems existing in the prior art, the present invention proposes a co-doped fluorescent material with anti-thermal quenching characteristics and a preparation method and application thereof, which are applied to non-contact temperature sensors to effectively expand the temperature measurement range and improve the detection sensitivity.

[0006] The technical solution adopted by the present invention is as follows:

[0007] Co-doped fluorescent material with reverse thermal quenching properties, its general chemical formula is: Na3Ca 4-x-y Tb x Eu y TeP3O 15 , where 0.01≤x,y≤0.2.

[0008] The method for preparing a co-doped fluorescent material with an anti-thermal quenching characteristic comprises mixing and grinding the raw materials corresponding to the molar ratio of elements Na, Ca, Tb, Eu, Te, and P in a ratio of 3:(4-xy):x:y:1:3, and then performing microwave solid phase synthesis to obtain Na3Ca 4-x-y Tb x Eu y TeP3O 15 ; Where 0.01≤x,y≤0.2.

[0009] Furthermore, the specific process of microwave solid phase synthesis is as follows: the ground sample is placed in a microwave solid phase reaction furnace, heated to 800°C to 900°C, sintered for 15 to 40 minutes, cooled to room temperature, taken out, ground into powder, and Na3Ca 4-x- y Tb x Eu y TeP3O 15 .

[0010] Furthermore, the elements Na, Ca, Tb, Eu, Te, and P correspond to Na source compounds, Ca source compounds, Tb source compounds, Eu source compounds, Te source compounds, and P source compounds, respectively.

[0011] Furthermore, the raw materials are specifically Na2CO3CaCO3, Tb2O3, Eu2O3, TeO2 and NH4H2PO4.

[0012] Furthermore, the temperature is raised to 800° C. to 900° C. at a rate of 10° C. / min to 30° C. / min during microwave solid phase synthesis.

[0013] Furthermore, during the heating process, the maximum setting power of the microwave solid phase reactor is not higher than 1400W, and the minimum setting power is not lower than 500W.

[0014] Furthermore, the maximum setting power of the microwave solid phase reactor during the heat preservation sintering process is not higher than 1200W, and the minimum setting power is not lower than 500W.

[0015] Furthermore, the grinding time is not less than 30 minutes.

[0016] Furthermore, the grinding is performed multiple times to reduce the agglomeration of the powder and eliminate the influence on the luminescence performance.

[0017] The present invention also provides the co-doped fluorescent material with reverse thermal quenching characteristics and the use of the co-doped fluorescent material with reverse thermal quenching characteristics obtained by the preparation method in a non-contact temperature sensor.

[0018] The beneficial effects of the present invention are:

[0019] 1. The co-doped fluorescent material with anti-thermal quenching characteristics proposed in the present invention has excellent thermal stability of luminescence and can meet the requirements of working under high temperature conditions. As the ambient temperature increases, the luminescence intensity shows a trend of first increasing and then decreasing, showing anti-thermal quenching characteristics;

[0020] 2. The co-doped fluorescent material with anti-thermal quenching properties proposed in the present invention can be applied to non-contact temperature sensors, wherein the doped terbium ions (Tb 3+ ) and europium ions (Eu 3+ ) are located at 545nm and 617nm respectively, and there is a functional relationship between the luminescence intensity of the two and the temperature that meets the requirements of non-contact temperature sensing materials; compared with the high-temperature thermal quenching effect, the anti-thermal quenching characteristics presented by the co-doped fluorescent material can further expand the temperature measurement range of the non-contact temperature sensor and significantly improve the temperature measurement sensitivity;

[0021] 3. The raw materials of the present invention are cheap, the production cost is low, the operation is simple, the device structure required for the reaction is simple, and it is suitable for mass industrial production;

[0022] 4. Preferably, when x=0.2 and y=0.07, the obtained co-doped fluorescent material with anti-thermal quenching characteristics has the best thermal stability, and is applied to non-contact temperature sensors, with an absolute sensitivity of 5.61×10 -2 K -1 , the relative sensitivity can reach 4.43%K -1 . BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The Na3Ca obtained in Example 1 3.73 TeP3O 15 :0.2Tb 3+ ,0.07Eu 3+Compared with the Na3Ca 3.8 TeP3O 15 :0.2Tb 3+ , Na3Ca obtained in Comparative Example 2 3.93 TeP3O 15 :0.07Eu 3+ Powder X-ray diffraction (XRD) comparison chart;

[0024] Figure 2 The Na3Ca obtained in Example 1 3.73 TeP3O 15 :0.2Tb 3+ ,0.07Eu 3+ Compared with the Na3Ca 3.8 TeP3O 15 :0.2Tb 3+ , Na3Ca obtained in Comparative Example 2 3.93 TeP3O 15 :0.07Eu 3+ Comparison chart of normalized integrated luminescence intensity spectra;

[0025] Figure 3 The Na3Ca obtained in Example 1 3.73 TeP3O 15 :0.2Tb 3+ ,0.07Eu 3+ Variable temperature emission spectrum in the temperature range of 298~573K;

[0026] Figure 4 The Na3Ca obtained in Example 1 3.73 TeP3O 15 :0.2Tb 3+ ,0.07Eu 3+ Luminescence intensity ratio spectrum;

[0027] Figure 5 The Na3Ca obtained in Example 1 3.73 TeP3O 15 :0.2Tb 3+ ,0.07Eu 3+ Absolute sensitivity and relative sensitivity plots. DETAILED DESCRIPTION

[0028] In order to make the objectives, technical solutions and advantages of the present invention more clear, the present invention is further described in conjunction with the following specific embodiments and with reference to the accompanying drawings.

[0029] Example 1

[0030] This embodiment prepares a co-doped fluorescent material with reverse thermal quenching properties, and its chemical formula is: Na3Ca 3.73 TeP3O 15 :0.2Tb 3+ ,0.07Eu 3+ (NCTP: 0.2Tb 3+ ,0.07Eu 3+ ).

[0031] The preparation method specifically comprises the following steps:

[0032] Step 1, accurately weigh each raw material according to the stoichiometric ratio, specifically 0.318g Na2CO3 (99.9%), 0.747g CaCO3 (99.9%), 0.319g TeO2 (99.9%), 0.690g NH4H2PO4 (99.9%), 0.0732g Tb2O3 (99.99%), 0.0246g Eu2O3 (99.99%);

[0033] Step 2: Mix all the raw materials and grind them in an agate mortar for multiple times, with each grinding time of 30 min to obtain a ground sample;

[0034] Step 3: Put the ground sample into a corundum crucible, and then put it into a microwave solid phase reactor, heat it to 850°C at a heating rate of 20°C / min, sinter it at 850°C for 20min, cool it to room temperature and take it out, grind it into powder several times, each grinding time is 30min, and finally obtain Na3Ca 3.73 TeP3O 15 :0.2Tb 3+ ,0.07Eu 3+ .

[0035] Furthermore, the maximum and minimum set power values ​​of the microwave solid phase reactor during the heating process are 1300W and 600W respectively; the maximum and minimum set power values ​​of the microwave solid phase reactor during the heat preservation and sintering process are 1200W and 500W respectively.

[0036] Example 2

[0037] This embodiment prepares a co-doped fluorescent material with reverse thermal quenching properties, and its chemical formula is: Na3Ca 3.73 TeP3O 15 :0.2Tb 3+ ,0.01Eu 3+ .

[0038] The preparation method thereof is different from that of Example 1 only in that the raw materials weighed in step 1 are adjusted to: 0.318g Na2CO3 (99.9%), 0.759g CaCO3 (99.9%), 0.319g TeO2 (99.9%), 0.690g NH4H2PO4 (99.9%), 0.0732g Tb2O3 (99.99%), and 0.0035g Eu2O3 (99.99%); the other steps remain unchanged.

[0039] Example 3

[0040] This embodiment prepares a co-doped fluorescent material with reverse thermal quenching properties, and its chemical formula is: Na3Ca 3.73 TeP3O 15 :0.2Tb 3+ ,0.2Eu 3+ .

[0041] The preparation method thereof is different from that of Example 1 only in that: the raw materials weighed in step 1 are adjusted to: 0.318g Na2CO3 (99.9%), 0.721g CaCO3 (99.9%), 0.319g TeO2 (99.9%), 0.690g NH4H2PO4 (99.9%), 0.0732g Tb2O3 (99.99%), 0.0703g Eu2O3 (99.99%), and the sintering temperature in step 3 is adjusted to 900°C, and the sintering time is adjusted to 15min; the other steps remain unchanged.

[0042] Example 4

[0043] This embodiment prepares a co-doped fluorescent material with reverse thermal quenching properties, and its chemical formula is: Na3Ca 3.73 TeP3O 15 :0.01Tb 3+ ,0.2Eu 3+ .

[0044] The preparation method thereof is different from that of Example 1 only in that the raw materials weighed in step 1 are adjusted to: 0.318g Na2CO3 (99.9%), 0.759g CaCO3 (99.9%), 0.319g TeO2 (99.9%), 0.690g NH4H2PO4 (99.9%), 0.0037g Tb2O3 (99.99%), and 0.0703g Eu2O3 (99.99%); the other steps remain unchanged.

[0045] Example 5

[0046] This embodiment prepares a co-doped fluorescent material with reverse thermal quenching properties, and its chemical formula is: Na3Ca 3.73 TeP3O 15 :0.01Tb 3+ ,0.01Eu 3+ .

[0047] The preparation method thereof is different from that of Example 1 only in that: the raw materials weighed in step 1 are adjusted to: 0.318g Na2CO3 (99.9%), 0.797g CaCO3 (99.9%), 0.319g TeO2 (99.9%), 0.690g NH4H2PO4 (99.9%), 0.0037g Tb2O3 (99.99%), 0.0035g Eu2O3 (99.99%), and the sintering temperature in step 3 is adjusted to 800°C, and the sintering time is adjusted to 40min; the other steps remain unchanged.

[0048] Comparative Example 1

[0049] This comparative example prepares a single-doped fluorescent material, whose chemical formula is: Na3Ca 3.8 TeP3O 15 :0.2Tb 3+ (NCTP: 0.2Tb 3+ ).

[0050] The preparation method thereof is different from that of Example 1 only in that the raw materials weighed in step 1 are adjusted to: 0.318 g Na2CO3 (99.9%), 0.761 g CaCO3 (99.9%), 0.319 g TeO2 (99.9%), 0.690 g NH4H2PO4 (99.9%), and 0.0732 g Tb2O3 (99.99%); the other steps remain unchanged.

[0051] Comparative Example 2

[0052] This comparative example prepares a single-doped fluorescent material, whose chemical formula is: Na3Ca 3.93 TeP3O 15 :0.07Eu 3+ (NCTP: 0.07Eu 3+ ).

[0053] The preparation method thereof is different from that of Example 1 only in that the raw materials weighed in step 1 are adjusted to: 0.318 g Na2CO3 (99.9%), 0.787 g CaCO3 (99.9%), 0.319 g TeO2 (99.9%), 0.690 g NH4H2PO4 (99.9%), and 0.0246 g Eu2O3 (99.99%); the other steps remain unchanged.

[0054] According to Figure 1 The powder X-ray diffraction spectrum comparison diagram shown in FIG. 3.73 TeP3O 15 :0.2Tb 3+ ,0.07Eu 3+ Compared with the Na3Ca 3.8 TeP3O 15 :0.2Tb 3+ , Na3Ca obtained in Comparative Example 2 3.93 TeP3O 15 :0.07Eu 3+ The position of the diffraction peak is similar to that of the simulated pure phase Na3Ca4TeP3O 15 The positions of the diffraction peaks correspond to each other, indicating that the synthesized materials are all pure phase Na3Ca4TeP3O 15 , and Tb 3+ With Eu 3+ The introduction of ions did not destroy the crystal structure of the matrix.

[0055] According to Figure 2 From the comparison diagram of the normalized integrated luminescence intensity spectra shown, it can be seen that the luminescence intensity of the single-doped fluorescent materials obtained in Comparative Example 1 and Comparative Example 2 decreases monotonically with increasing temperature, showing a high-temperature thermal quenching phenomenon; the co-doped fluorescent material obtained in Example 1 shows that: with increasing temperature, the luminescence intensity first increases and then decreases, with obvious reverse thermal quenching phenomenon.

[0056] Figure 3 The Na3Ca obtained in Example 1 3.73 TeP3O 15 :0.2Tb 3+ ,0.07Eu 3+ The temperature-dependent emission spectrum in the temperature range of 298-573K, doped Tb 3+ and Eu 3+ The luminescence centers of Tb are located at 545nm and 617nm respectively. 3+ With Eu 3+ The luminous intensity variation trends of Eu 3+ The luminous intensity of Tb changes with temperature more obviously than that of3+ The luminous intensity of the sensor changes with temperature, and thus produces a significantly different intensity response trend to temperature, indicating that it can be applied to non-contact temperature sensors based on luminous intensity ratio.

[0057] Figure 4 The Na3Ca obtained in Example 1 3.73 TeP3O 15 :0.2Tb 3+ ,0.07Eu 3+ The luminescence intensity ratio spectrum of Na3Ca 3.73 TeP3O 15 :0.2Tb 3+ ,0.07Eu 3+ The nonlinear fitting effect judgment parameter R of the luminous intensity ratio LIR of 545nm and 617nm in the range of 298~573K 2 It can reach 0.995, indicating that the nonlinear fitting effect is good and suitable for temperature detection.

[0058] Figure 5 The Na3Ca obtained in Example 1 3.73 TeP3O 15 :0.2Tb 3+ ,0.07Eu 3+ The absolute sensitivity (S a ) and relative sensitivity (S r ) spectrum, it can be seen that S in the range of 298~573K a Value and S r The values ​​are high, and S a The maximum value can reach 5.61×10 -2 K -1 , S r The maximum value can reach 4.43%K -1 , which is significantly superior to the absolute sensitivity and relative sensitivity of traditional co-doped fluorescent materials based on high-temperature thermal quenching phenomenon, and has a wide temperature measurement range. It can be applied to non-contact temperature sensing technology and can effectively improve the detection range, accuracy and sensitivity of non-contact temperature sensors.

[0059] The above embodiments only illustrate the principles and advantages of the present invention, and are not intended to limit the present invention. They are only intended to help understand the principles of the present invention. The protection scope of the present invention is not limited to the above configurations and embodiments. Those skilled in the art can make various other specific modifications and combinations based on the disclosed technology without departing from the essence of the present invention, but they are still within the protection scope of the present invention.

Claims

1. A co-doped fluorescent material having an anti-thermal quenching property, characterized in that: Its chemical formula is: Na3Ca 4-x- y Tb x Eu y TeP3O 15 , where 0.01≤x,y≤0.

2.

2. A method for preparing a co-doped fluorescent material having an anti-thermal quenching property, characterized in that: Na3Ca was synthesized by mixing and grinding the raw materials corresponding to the molar ratio of Na, Ca, Tb, Eu, Te, and P in a ratio of 3:(4-xy):x:y:1:3, and then subjected to microwave solid phase synthesis. 4-x-y Tb x Eu y TeP3O 15 ; Where 0.01≤x,y≤0.

2.

3. The method for preparing the co-doped fluorescent material with reverse thermal quenching characteristics according to claim 2, characterized in that: The specific process of microwave solid phase synthesis is as follows: the ground sample is placed in a microwave solid phase reactor, heated to 800℃~900℃, sintered for 15~40min, cooled to room temperature and taken out, ground into powder, and Na3Ca 4-x-y Tb x Eu y TeP3O 15 .

4. The method for preparing the co-doped fluorescent material with reverse thermal quenching characteristics according to claim 3, characterized in that: During the microwave solid phase synthesis, the temperature is raised to 800°C to 900°C at a rate of 10°C / min to 30°C / min.

5. The method for preparing the co-doped fluorescent material with reverse thermal quenching characteristics according to claim 2, characterized in that: The elements Na, Ca, Tb, Eu, Te, and P correspond to Na source compounds, Ca source compounds, Tb source compounds, Eu source compounds, Te source compounds, and P source compounds, respectively.

6. The method for preparing the co-doped fluorescent material with reverse thermal quenching characteristics according to claim 2, characterized in that: The specific raw materials are Na2CO3, CaCO3, Tb2O3, Eu2O3, TeO2 and NH4H2PO4.

Citation Information

Patent Citations

  • Luminescent materials based on cerium and europium activated aluminosilicates, their preparation methods and applications

    CN113004892B

  • Preparing method of rare-earth-ion doped metal-organic framework fluorescent material

    CN109796477A

  • Dysprosium europium co-doped tellurium phosphate fluorescent powder for white light LED and microwave solid-phase synthesis method thereof

    CN115491202A